FKKSA undergraduate research project module - Sumaiya, Zainal Abidin; Nurul Aini, Razali; Rohaida, Che Man; Nurul Sa'aadah, Sulaiman; Hamidah, Abdullah (Penerbit UMP, 2017)

(untitled)
This module is divided into 2 parts; the URP 1 and URP 2 and each part is sub-divided into 4 chapters i.e. workflow, formats and organization, rubrics and log book. This module will be used for two semesters of URP. We hope this module could benefits the students and guide them to complete their undergraduate research project.